Pengelolaan Zakat Profesi Dalam Tinjauan Hukum Islam dan Undang-undang Republik Indonesia Nomor 23 Tahun 2011 (Studi Kasus Di LAZIS Muhammadiyah Solo) - Hanif, Ibrohim; , Drs. Harun, MH. (2016)
Zakat on profession is an obligation that Muslims should complete it when their incomes achieving niṣāb and ḥaul. Many institutions of zakat management have been established with a shared goal, namely to be a facility for mustaḥiq in performing obligation of paying zakat and it is accompanied with the issue of law on zakat that can be a basic reference in establishment of legal institution of zakat management in attempts of distributing funds obtained from zakat, infaq and shadaqah. Therefore, purpose of the research is to describe clearly the matters concerning of management of zakat on profession conducted by Lembaga Amal Zakat dan Shadaqah Muhammadiyah (LAZISMU) of Solo. Author sought to review it from viewpoint of Islamic law and Law No. 23 of 2011 of Indonesian Republic on collection and use of zakat on profession. The research is field one. Based on its type and purpose, the research is a descriptive-qualitative one, namely an analysis that is describing a situation or a phenomenon in words or sentences, and then division is conducted according to categories in order to arrive at a conclusion. Data is collected by using observation, interview and documentation, and the data is analyzed inductively. Based on the research, author concluded that the practice of management of zakat on profession by LAZISMU of Solo is in accordance with Islamic Law and Law no. 23 of 2011 of Indonesian Republic and it can be proved with the periodic use of audit system by the Badan Amil Zakat Nasional (BAZNAS).